ADVANCED CONTROL FOR PHOTOVOLTAIC-UNIFIED POWER QUALITY CONDITIONER SYSTEMS: A SIMULATION APPROACH (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
This paper presents the design and evaluation of a three-phase photovoltaic-unified power quality conditioner (PV-UPQC), integrating series and shunt compensators via a shared DC link. The system combines distributed generation with active power filtering, where the shunt compensator harvests PV power and compensates for harmonic currents and reactive power from nonlinear loads. Harmonic identification uses p-q theory, with experiments conducted under real solar irradiation in Algeria’s Adrar region. The shunt active power filter (ShAPF) compensates for harmonics and reactive power while optimizing PV power extraction at the maximum power point (MPP). Adaptive neuro-fuzzy inference systems (ANFIS) and sliding mode control (SMC) are combined to reduce chattering and enhance PV energy extraction. Simulations show SMC/ANFIS outperforms conventional SMC.
Keywords: Unified power quality conditioner (UPQC); P-Q theory; Photovoltaic (PV) system; Sliding mode control (SMC); Adaptive neuro-fuzzy inference (ANFIS) systems